Investment analysis of solar power plant installation on the roof of the central business district office building with the best investment value - Soejanto, Irwan; Poerbaningrat, Raden Muhammad Nalindra; Ristyowati, Trismi; Puryani, Puryani (OPSI, 2024)
The Central Business District (CBD) office building is making efforts to reduce building electricity costs, and one alternative is solar power plant installation. PT. Rancang Prima Sejahtera, engaged in the solar energy industry, conducts consulting services with Central Business District office buildings, so PT. Rancang Prima Sejahtera made an indicative proposal with several solar power plant installation scenarios to be installed on the roof of the Central Business District office building. Four scenarios are created from the combination of 2 PV modules and two inverters. Each scenario created will be assessed for the level of opt, and the investment value will be calculated. In combining components using the principles of the Vereun Deutsche Ingineuer (VDI) 2222 method and assessed each scenario using six aspects of assessment.Meanwhile, the investment analysis assessment uses the parameters of Cost of Energy (CoE), Net Present Value (NPV), Internal Rate of Return (IRR), Benefit-Cost Ratio (B-CR), and discounted payback period. The results of the analysis conducted found that the third scenario was the best scenario with a percentage of the design value of 82.5%, CoE value of Rp398.31/kWh, NPV value of Rp2,451,719,005, IRR percentage of 23.75%, B-CR value of 7.8, and DPP value for 6.8 years with a project life of 30 years. The findings of the investment research indicate that the implementation of solar power plant installations in office buildings located in Central Business Districts yields long-term cost reductions in electricity expenses over a 30-year period, as opposed to relying solely on the services provided by the State Electricity Enterprise.